Fannia Robineau-Desvoidy (Diptera: Fanniidae) of Colombia: new species, identification key and updated checklist - Durango, Yesica; Ramírez-Mora, Manuel (Zootaxa, 2019)
The genus Fannia Robineau-Desvoidy is a group of calyptrate Diptera distributed in all biogeographic regions and comprises about 300 species. The present study described five new species from Colombia: Fannia aburrae sp. nov., Fannia copacabana sp. nov., Fannia isa sp. nov., Fannia pseudoconstricta sp. nov., Fannia spinosa sp. nov. Male specimens are described, and morphological characters and terminalia are illustrated. Likewise, an updated identification key for males and an updated checklist for the 37 species present in Colombia are provided. New records are presented for the country.